Four new species of Wahnesia Förster, 1900 from the D’Entrecasteaux, Louisiade and Woodlark island groups, Papua New Guinea (Odonata: Argiolestidae) - Polhemus, Dan A.; Kalkman, Vincent J. (Zootaxa, 2021)
The species of the damselfly genus Wahnesia Förster, 1900 occurring in the D’Entrecasteaux Islands, Louisiade Archipelago, and on Woodlark Island are reviewed, and four new species are described: W. muyuw from Woodlark Island, W. misima from Misima Island, W. tagula from Tagula (Sudest) Island, and W. rossel from Rossel Island, these latter three islands all lying in the Louisiade Archipelago. In addition, new information is presented on the identification and distribution of the two previously described species from the D’Entrecasteaux islands: W. annulipes (Lieftinck, 1956) from Goodenough, Fergusson, and Normanby islands, and W. armeniaca (Lieftinck, 1956) from Goodenough and Fergusson islands. Illustrations are provided for the male abdominal terminalia and genital ligula of the four new species, as well as the wings and a color photograph of a live male of W. muyuw, and the ligula of W. armeniaca, accompanied by updated distribution maps for all species treated.